102k views
6 votes
Solve each system by substitution.
y = 2x + 5
3x - y= -6

User Apaatsio
by
5.2k points

1 Answer

4 votes
x=-1 and y=3

To solve this, because y is equal to 2x+5, you can substitute 2x+5 into the bottom equation for y.

You now have 3x - (2x + 5) =-6

This can be solved like a normal equation. Multiply each term in the parenthesis by -1.

3x - 2x - 5 = -6

Subtract 2x from 3x

x - 5 = -6

Add 5 to both sides

x=-1

Now you can solve for y by plugging -1 in for x in either equation. Im going to use the top one.

y= 2(-1)+5
y= -2+5
y=3

You can check your answer by plugging in the values for x and y into both equations and making sure both sides equal each other.
User Gjohn
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.